The Neglected Stepchild: Military Justice and Democratic Transition in Chile - Pereira, Anthony (Social justice, 2005)
Part of a special issue on the many faces of violence. The writers challenge the conventional wisdom about judicial reform in Chile following the country's democratic transition. The assert that this reform can only be characterized as a success by ignoring the issue of military justice, a system that affects many citizens. They point out that, even though important progress has been made in other areas of the legal system, an enlarged and insulated system of military courts still rewards the armed forces with special prerogatives that violate the principle of equality before the law.